A hystory of love and hate: the royal administration in Cape Verde and the General Company of Grão-Pará and Maranhão (1757-1777) (Ágora Journal, 2021)
In this article, I intend to discuss the perception among the officers of the Portuguese royal administration, sent to the management of the Cape Verde archipelago, of the Companhia Geral do Grão-Pará e Maranhão's (henceforth CGPM) performance. To this end, I intend to base this work mainly on separate documentation from the Overseas Historical Archive in Portugal and on specific documentation that has already been published or is safeguarded in the Arquivo Nacional da Torre do Tombo e and in the Arquivo Nacional do Tribunal de Contas. Through this documentation, I intend to demonstrate the troubled relationship that exists between the officers sent to administer the archipelago, island residents, administrators and the monopoly company's Board of Directors. This work is divided into two parts: in the first, we will talk about the occupation and economy of the Cape Verdean archipelago; in the second part, which is the core of the article, we will show the conflicting relationship between administrators and CGPM.
Keywords: Overseas Administration - General Company of Grão-Pará and Maranhão - Cape Verde Islands